Applications of Computational Methods in Manufacturing and Product Design Select Proceedings of IPDIMS 2020 - Deepak, B. B. V. L.; Parhi, D.R.K.; Biswal, B.B.; Jena, Pankaj C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents the select proceedings of the conference of Innovative Product Design and Intelligent Manufacturing System (IPDIMS 2020), held at the National Institute of Technology, Rourkela, India. The book addresses latest methods and advanced tools from different areas of design and manufacturing technology. The main topics covered include computational methods for robotics, mechatronics and human-computer interaction; computer-aided design, manufacturing and engineering; aesthetics, ergonomics and UX/UI design; smart manufacturing and expert systems. The contents of this book will be useful for researchers as well as professionals working in the areas of industrial design, mechatronics, robotics, and automation.
Aesthetical Design of a Bio-inspired Futuristic Vehicle for Smart Transportation -- Detection and Counting of Nuts & Bolts with Image Processing using Mat lab -- Evaluation of EDM Die-Sinking Electrode Wear rate of COOH-MWCNT/Al nanocomposite -- Agribots concepts and operations-A review -- A Review of Sensors for Measuring Soil Parameters Supporting Agricultural Practices.
Keywords: Industrial engineering; Production engineering; Computer-aided engineering; Control engineering; Robotics; Automation; Industrial and Production Engineering; Computer-Aided Engineering (CAD, CAE) and Design; Control, Robotics, Automation; Product design -- Congresses; Artificial intelligence -- Industrial applications -- Congresses; Manufacturing processes -- Congresses